The Big 5 Personality Towards Product Design In Kansei Engineering - Syafika, Ainul; Khairunisya, Nur; Sihombing, Haery; Sulaiman, Shamsudin; M.R, Salleh; M Y, Yuhazri (International Journal of Engineering and Technology, 2018)
This study discussed the features and the design preferences of the product in order to find the priority of the product towards the profile design of the car beside the correlation analysis of the Big 5 Theory. The purpose of this study is to find out what personal traits and originality of personal behavior of perception towards the understanding of human psychology related to the product design. Questionnaires that consist of each aspect of articulated customer expression in 5 Kansei words (stylish, comfortable, safe, sporty and luxury) towards 2 car design type (City and Sedan) were utilized. Statistical analysis was utilized to evaluate data from 171 respondents on their individual needs and behavior. The result shows that the preferences of product design were related to customerâ€™s emotional feelings in which customers' personality traits (Agreeableness) based on The Big 5 test is having significant correlation towards Safe and Sporty for City and Sedan Car respectively. Based on these finding, the customers' personality traits can use employed to predict what the customer expression towards the product design.Â